The effect of moderate altitude on objective and subjective systems of training load quantification - Feriche, B.; Rodriguez, F. A.; Iglesias, X.; Calderon, C.; Barrero, A.; Perez-Medina, I.; Barrero, A.; Vazquez, J.; Abalos, X.; Rodriguez-Zamora, L.; Truijens, M. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Objective and subjective training load indicators, such as training impulses (TRIMPs) and ratings of perceived exertions (RPE) have been used to monitor elite swimmersunder normoxic conditions (Wallace et al., 2009). However, their usefulness and validity under hypoxic conditions has not been studied to date. This study aims to analyse the effect of 3-weeks exposure to moderate altitudeon the relationship between objective (TRIMPs) and subjective (s-RPE) systems of training load quantification in elite swimmers. Methods: 40 elite swimmers were assigned to two groups: Lo, who lived and trained at sea level, and Hi, who lived and trained at moderate altitude (CAR Sierra Nevada, Spain, 2320 m above sea level). During three consecutive weeks all training sessions were monitored. Heart rate(HR) and time were recorded to compute TRIMPs (Banister& Hamilton, 1985).Session-RPE(s-RPE) based on the CR-10 scale (Foster et al. 2001) was self-administered within 30 min after each swimming (S1, S2) and dry-land (Dl) training sessions. Results: There were no differences in S1 and S2 training loads (TRIMPs)in any of both Hi and Lo groups.s-RPE showed differences between groups that were significantlysmaller in the Hi group in S1(p<0.001). In Dl differences were noted between both groups in all training sessions (P<0.05).The association (Pearson`s) between s-RPE and TRIMPs during swimming sessions was moderate both in S1(Hi: 0.42; Lo: 0.76; p<0.001) and S2 (Hi: 0.69; Lo: 0.56; p<0.001).In Dl sessions no we did not find an association between methods (Hi: 0.02; Lo: 0.02; p> 0.05). Discussion: The relationship between TRIMPs and s-RPE training load indicators is low-moderate. Therefore, we consider they should not be used indiscriminately in altitude, at least during the acclimatization phase. s-RPE appears to be more sensitive to an increase in the intensity of the internal load than to a rise in training volume (Sweet et al., 2004).This is supported by our observation that there were differences in s-RPE between the Hi and the Lo groups inthe first two weeks, but not in third week when training intensity tend to equalize. TRIMPs do not seem to constitute an appropriate quantification procedure for workload during dry-land sessions.